Literacy Read and Write in the Application of the Independent Curriculum - Andas Nidaa'an Khofiyya; Lilik Binti Mirnawati; Fajar Setiawan (Universitas Pendidikan Ganesha, 2023)
The government succeeded in designing the curriculum but the obstacles in literacy, mathematics, and science were constrained in implementation so that further performance was held. This study aims to analyse the independent curriculum's implementation on literacy in Indonesian language skills in grade 4 elementary school. This type of research is qualitative. The approach used is a qualitative research approach. Participants in this study were students in grade 4 (four) elementary schools, teachers, and principals. Data collection techniques were carried out through data triangulation (combined). The instrument used in collecting data is a questionnaire. The data analysis technique consists of data collection, data reduction, presentation of data, and concluding/verification. The study results prove that the pattern of applying the independent curriculum to literacy in Indonesian language lessons in grade 4 can be used with 4 (four) applications. First, there is literacy training both in class and outside the classroom. Second, parenting students. Third, collaboration between class teachers and school principals regarding school programs implemented in class. Fourth is the habit of reading. With these four applications, it is hoped that students' literacy skills can be evenly distributed throughout Indonesia so that the generation of the Indonesian nation can become the younger generation by producing the best achievements.